Kontribusi Wakaf Dalam Membangun Peradaban Dunia Islam Dan Barat (Studi Pada Lembaga Pendidikan Tinggi) - Putra, Trisno Wardy; Hasaruddin, Hasaruddin; Susmihara, Susmihara (Studia Economica : Jurnal Ekonomi Islam, 2024)
Waqf is a form of worship that has a major contribution to world civilization. This research aims to analyze the role of waqf in building Islamic and Western civilization in higher education institutions. The method used is qualitative with a literature study approach, namely understanding and studying theories from various literature related to research. The research results show that Islamic education cannot be separated from the role of waqf. One proof of higher education built from waqf is Al-Qarawiyyin University in Morocco. This university has been named the oldest and first campus to use waqf. The concept of waqf developed and was adopted by the western world with the term endowment fund. Harvard University is an example of a university built from endowment funds. Indonesia is one of the countries that has also practiced waqf at higher education institutions, but has not been able to provide free education to underprivileged students. This research is an original study to motivate the Muslim community to be more enthusiastic about giving waqf to higher education. This study is also very important for practitioners and policy makers in evaluating the potential and role of waqf in developing Islamic higher education institutions